The association between allostatic load and anthropometric measurements among a multiethnic cohort of children. Issue 6 (17th January 2019) - Cedillo, Yenni E.; Murillo, Anarina L.; Fernández, José R.
Summary: Objective: This study investigated if levels of allostatic load (ALoad) differed according to race/ethnicity in children and if ALoad was associated with obesity‐related measures. Methods: A multiethnic sample of 307 children aged seven to 12 was evaluated, composed of 39% European American (EA), 35% African American (AA), and 26% Hispanic American (HA) youth. Anthropometric measurements were evaluated by dual‐energy X‐ray absorptiometry, and other measurements included body mass index (BMI) and waist circumference (WC). Allostatic load scores were estimated based on two different calculations, including seven and eight biomarkers (ALoad1 and ALoad2), respectively. Analyses of variance, independence tests, and multiple regression models were performed. Results: From the total sample, 22.80% (n = 70) of children were characterized as "no load, " 46.58% (n = 143) "low load, " and 30.62% (n = 94) "high load." Hispanic American children showed the highest ALoad scores (2.07 ± 1.54; 95% CI, 1.73‐2.41) compared with AA children (1.71 ± 1.43; 95% CI, 1.43‐1.99) and EA children (1.56 ± 1.34; 95% CI, 1.32‐1.80) ( P < 0.05). Higher scores of ALoad (using both ALoad1 and ALoad2 calculations) were associated with higher BMI, total body fat mass, body percent fat, and WC ( P < 0.05). Conclusion: Significant differences in ALoad were observed in children according to race/ethnicity. Increased exposure to stressors captured by ALoad may result in increased risk for excessive adiposity and potential health risk in children. Further, ALoad may serve as a preventive marker for conditions known to continue throughout adulthood.